Glass and glass production in the Near East during the Iron Age : evidence from objects, texts and chemical analysis - Schmidt, Katharina, (Archaeopress archaeology., 2019)
Glass and Glass Production in the Near East during the Iron Age Period' examines the history of glass in Iron Age Mesopotamia and neighbouring regions (1000-539 BCE). This is the first monograph to cover this region and period comprehensively and in detail and thus fills a significant gap in glass research. It focuses on an identification of the different types of glass objects and their respective manufacturing techniques that existed in the Iron Age period. Both the material glass and individual glass objects are investigated for such topics as how raw glass (primary production) and glass objects (secondary production) were manufactured at that time, how both these industries were organized, and how widespread glass objects were in Mesopotamian society in the Iron Age period. Such a comprehensive picture of glass and its production in the Iron Age can only be achieved by setting archaeological data in relation to cuneiform texts, archaeometric analyses and experimental-archaeological investigations. With regard to the different disciplines incorporated into this study, an attempt was made to view them together and to establish connections between these areas.